Sustainable Finance: Political Challenges of Development and Implementation of Framework Conditions - Claudia Kemfert; Sophie Schmalz (Green Finance, 2019)
According to the 2015 Paris Agreement, a long-term goal is the commitment to “making finance flows consistent with a pathway towards low greenhouse gas emissions and climate-resilient development.” Reconciling climate change objectives and financial flows is an enormous challenge in the 21st century. States in general and Germany in particular have various instruments at their disposal to initiate appropriate measures. On the one hand, the state can exert direct influence by orienting its own activities towards sustainability, for example by meeting sustainability standards for investments and participations by public institutions and by anchoring divestment strategies in law. On the other hand, the development of suitable framework conditions is a requirement for encouraging private financial market players towards sustainability.A key requirement for the development of sustainable financial system is a uniform taxonomy of sustainability. Standards and labels for identifying business activities can then be implemented. The development of political framework conditions is currently facing far-reaching challenges at European and national level: There is a risk that current approaches will only be applied to a limited extent. Sustainable investments currently account for approximately 3% of the total market (2017).This article aims to focus on the extent to which policy frameworks currently being developed at national and European level can contribute to the development of sustainable finance. In addition to the challenges of implementing and developing new policy approaches, the limits of existing instruments will be identified. Beyond the indirect influence of the state, investment strategies and criteria of public institutions and procurement are analysed, which represent a direct influence of the state for the development of a sustainable financial sector. A case study on the Divestment Strategies is used for this purpose.
Keywords: G18; G23; 330; Sustainable finance; ESG; Divestment; Procurement; European Union